A sustainable supply chain model with price and advertisement dependent demand utilizing a hybrid carbon policy and multi-trade credit in an inflationary environment - S. R. Singh; Ummeferva Zaidi (Discover Sustainability)
Abstract Carbon emissions are a key driver of global warming. In today’s business landscape, organizations must collaborate to manage the increasing levels of carbon emissions while ensuring sustainable financial gains. Green inventory management minimizes the environmental impact of operations without compromising profitability. This paper develops a two-echelon sustainable supply chain model with one manufacturer and one retailer to address the pressing challenges of carbon emissions, inflation, and evolving consumer demand influenced by price and advertising. A hybrid carbon policy combining carbon tax and cap-and-trade mechanisms is incorporated to mitigate greenhouse gas emissions effectively. Additionally, the model integrates multi-trade credit policies to enhance financial flexibility for retailer. A mathematical model is proposed to determine optimal selling price, cycle time, advertisement frequency, and green investment under these considerations. The study validates the model through numerical examples and sensitivity analysis, revealing a significant reduction in carbon emissions: 2158.39 units under the hybrid carbon policy compared to 2166.77 units for carbon tax and 2165.60 units for cap-and-trade. These results underscore the hybrid carbon policy's superior environmental performance. Additionally, green investment and effective advertising significantly enhance profitability and sustainability, offering actionable insights for supply chain managers in an inflationary environment.